Efektivitas Pengelolaan dan Pembinaan Pasar Inpres Tanjung Tiram Berdasarkan Perda Nomor 6 Tahun 2016 Perspektif Siyasah Dusturiyah - Al Fahmi, Muhammad; Lubis, Syofiaty (UNES Law Review, 2024)
Market management and development in several areas has been carried out optimally, such as in the Medan City area. However, in the Tanjung Tiram Inpres market there are still several problems that have not been resolved. Regional Regulation Number 6 of 2016 concerning Market Management still has not achieved unity between law and society, which can cause obstacles to market management and development. Market effectiveness can be assessed based on the market management carried out, such as repairing public toilets, repairing market buildings such as kiosks, stalls and courtyards. Good lighting and security must also be considered, so that traders feel safe. The government must go directly to the field to monitor market developments so that it can take the right policies. Dialogue with the Market Association and traders must also be carried out to find out and resolve the problems faced. The government should have made regulations regarding Regional Market Companies (PD) so that PD Markets are available in every market in Batubara Regency. This will help with more effective and efficient market management and development.